Acute cannabis toxicity. (3rd August 2019) - Noble, Matthew J.; Hedberg, Katrina; Hendrickson, Robert G.
Abstract: Objective: We describe the clinical effects of, and products associated with, acute exposures to cannabis during the early legalization period of recreational cannabis in Oregon and Alaska. Methods: This was an observational study of Oregon/Alaska Poison Center data between 4 December 2015 and 15 April 2017. A standardized data collection instrument was created for this study that captured information about cannabis product description, route of exposure, intentional vs unintentional exposure, product dose, product manufacture source, product ownership source, initial vital signs, clinical signs and symptoms, and subject disposition. Subjects were included if the Poison Center received a call about an acute exposure to cannabis from the subject, subject's family member or friend, or healthcare worker participating in the subject's care. Subjects were excluded if there was no evident exposure, the exposure was chronic, there were co-ingestants, or the subject was non-human (e.g. pet). Results: Two hundred fifty three individuals were acutely exposed to cannabis (median age 20 years; range 8 months – 96 years; 54.2% males): 71 (28.1%) children (<12 years), 42 (16.6%) adolescents (12–17 years), and 140 (55.3%) adults (≥18 years). Children were most likely to unintentionally (98.6%) ingest (97.2%) homemade (35.2%) edibles (64.8%) belonging to a family member (73.2%) and experience sedation (52.1%). Adults were most likely to intentionally (88.6%) ingest (66.4%) retail (40.0%) edibles (48.6%) and experience neuroexcitation (47.1%). Adolescents' exposures had similarities to both adult and children; they were most likely to intentionally (81.0%) ingest (50.0%) homemade (23.8%) edibles (45.2%) belonging to a friend (47.3%) and to experience either neuroexcitation (42.9%) or sedation (40.5%). Among all ages, tachycardia and neuroexcitation were more likely following inhalation exposures compared to ingestions. Eight subjects were admitted to an intensive care unit, including three patients who were intubated; one subject died. Edibles were the most common products to cause symptoms in all age groups, while concentrated products were more likely to lead to intubation, especially when ingested. Children in particular had a higher likelihood of intensive care unit admission and intubation following exposure to concentrated products. Conclusions: Neurotoxicity is common after acute cannabis exposures. Children experienced unintentional exposures, particularly within the home and occasionally with major adverse outcomes. Concentrated products such as resins and liquid concentrates were associated with greater toxicity than other cannabis products. These findings may help guide other states during the early retail cannabis legalization period.